Toolkit for design research & interventions - Rooijackers, Margo, ....-; Marée, Geoff, ....-; Camargo-Borges, Celiane, ....- (Breda : Breda University of Applied Sciences, 2017)
This toolkit aims at supporting students interested in Imagineering. An Imagineer is (1) researcher, (2) facilitator/ designer and (3) director of human experiences & interactions. The ultimate goal of the Imagineer is to realise sustainable (social) change. By presenting a collection of methods and techniques that are useful within Imagineering research a new spectrum of possibilities opens up. The focus of the selection is on tools on the interface of research and design that facilitate processes of co-creation and collective creativity.